Pendidikan Kewirausahaan di Vokasional Pondok Tremas Pacitan (Analisa Kebijakan Pendidikan) - Achmad Ridlowi (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2021)
In the world of entrepreneurship education it must also be taught to students because entrepreneurship is one of the alternative ways to reduce the high unemployment rate in Indonesia, such as one of the students, not all students who have graduated from pesantren will continue to higher education, but there are alumni who are still unemployed and immediately work, therefore students need to be given life skills to deal with the outside world after graduating, which in this case at Pondok Pesantren Tremas Pacitan has provided skill activities through vocational skills and provides insight into entrepreneurship to the students with the aim that students who are become alumni ready to compete and be able to face the outside world, whether in any case. In connection with this statement, the researcher wants to know an example of the development of entrepreneurship education at Pondok Tremas Pacitan. The results showed that the development of entrepreneurship education for students at Pondok Tremas Pacitan was carried out through providing entrepreneurial motivation, insight into knowledge about entrepreneurship, entrepreneurship seminars and vocational skills activities such as: a). food processing, b). precious stone crafts, c). basic automotive training, d). TI computer, this activity aims to develop students' knowledge of entrepreneurship and talents and skills that can spur students to train skills to be enthusiastic about opening their own business so that students can be more and have provisions to improve. social life for the better.